The end of the professions? : the restructuring of professional work - Broadbent, Jane.; Dietrich, Michael; Roberts, Jennifer, 1966- (London ; New York : Routledge, 1997)
Professions and professional activity are undergoing dramatic changes as we approach the millennium. This interdisciplinary volume presents an overview of conceptual issues and considers the practical issues facing professionals today. It has two key objectives: to understand the nature of the changes in professional activity; and to see this restructuring in the context of wider socio-economic processes. Examining the professional areas of medicine, education, law and accountancy, the authors illustrate how the nature of professional activity is changing: decision-making power is being shifted away from the holders of specialised knowledge and towards clients and managers. Although this might seem to signify an end to traditional notions of professionalism involving trust, responsibility and self-organisation, they argue that this does not necessarily mean an end to professionalism itself, but rather a restructuring of its significance and functioning.
1. The end of the professions? / Jane Broadbent, Michael Dietrich and Jennifer Roberts -- 2. Beyond the economics of professionalism / Michael Dietrich and Jennifer Roberts -- 3. 'Accounting logic' and controlling professionals: The case of the public sector / Jane Broadbent and Richard Laughlin -- 4. Leading professionals: Towards new concepts of professionalism / Robin Middlehurst and Tom Kennie -- 5. Professionalism and medicine / Rosalind Eve and Paul Hodgkin -- 6. Regenerating professionalism within the academic workplace / Jon Nixon -- 7. Professional disintegration? The case of law / Gerard Hanlon and Joanna Shapland -- 8. A shifting professionalism: An examination of accountancy / Gerard Hanlon -- 9. Professionalism and politics: Towards a new mentality? / David Marquand.
Includes bibliographical references and index.
Shakib
Keywords: Professional corporations -- Management; Corporate reorganizations